The Selected Works of Isaac of Stella: A Cistercian Voice from the Twelfth Century - Dietz, Elias (Cistercian studies quarterly, 2008)
The article reviews the book "The Selected Works of Isaac of Stella: A Cisterian Voice from the Twelfth Century," by Daniel Deme.